2008
DOI: 10.1242/jcs.021006
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix retention of thrombospondin 1 is controlled by its conserved C-terminal region

Abstract: domain or type 1 repeats. Using a novel mRFP-tagged TSP1 C-terminal trimer, we demonstrate that ECM retention involves the RGD site and a novel site in the L-lectin domain with structural similarity to the ligand-binding site of cargo transport proteins. CD47 and ␤1 integrins are dispensable for ECM retention, but ␤1 integrins enhance activity. These novel data advance concepts of the molecular processes that lead to ECM retention of TSP1. Journal of Cell Science Matrix retention of thrombospondinsTSP2 is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 82 publications
5
50
0
Order By: Relevance
“…Further studies have confirmed this binding and binding of recombinant C-terminal regions of TSP1 to cell surface CD47 (70). However, a recombinant extracellular domain of CD47 expressed in bacteria failed to bind to TSP1 (71). This may be explained by incorrect folding of the recombinant CD47 domain or involvement of a long range disulfide bond not present in that construct (72,73), but our results suggest that post-translational modification with heparan sulfate may also be required for high affinity binding of TSP1 to CD47.…”
mentioning
confidence: 81%
“…Further studies have confirmed this binding and binding of recombinant C-terminal regions of TSP1 to cell surface CD47 (70). However, a recombinant extracellular domain of CD47 expressed in bacteria failed to bind to TSP1 (71). This may be explained by incorrect folding of the recombinant CD47 domain or involvement of a long range disulfide bond not present in that construct (72,73), but our results suggest that post-translational modification with heparan sulfate may also be required for high affinity binding of TSP1 to CD47.…”
mentioning
confidence: 81%
“…One puzzling aspect concerning CD47 is that much of the data on thrombospondin binding is from peptide binding analysis but the structure of the relevant thrombospondin domain shows that the peptides are in the core of the domain and not readily accessible [11]. This domain shows no affinity for the extracellular IgSF domain of CD47 [12] but direct binding of comparable proteins to CD47 at the cell surface has recently been shown [13] which might indicate that other parts of CD47 are involved. CD47 interactions and signalling are complex and beyond detailed analysis in this review.…”
Section: Introductionmentioning
confidence: 99%
“…Of the two CD47 binding VVM motifs identified in this domain of TSP1, the first is conserved among all five TSPs, suggesting that CD47 binding could be a universal attribute of this family (21). Based on structural evidence that the VVM motifs may not be accessible (22,23), however, conservation of VVM motifs may not be sufficient to predict CD47 binding. Uncertainty regarding the location of the CD47 binding site in the G domain of TSP1 therefore limits interpretation of the known sequence homology to predict CD47 binding to other TSP family members.…”
mentioning
confidence: 98%